Organoids From Mucinous Appendiceal Adenocarcinomas as High-Fidelity Models for Individual Therapy - Liu, Guangyao; Xiao, Xing; Xia, Yujian; Huang, Weibing; Chen, Wei; Xu, Jiannan; Chen, Songyao; Wang, Huijin; Wei, Jitao; Li, Huan; Shu, Man; Lu, Xiaofang; et al. (Frontiers in Medicine, 2022)
Background Mucinous appendiceal adenocarcinoma (MAA) is a rare, heterogeneous disease. Patients with unrespectable mucinous appendiceal adenocarcinoma presenting with peritoneal spread are treated by intraperitoneal chemotherapy, hyperthermic intraperitoneal chemotherapy, systemic chemotherapy, or targeted therapy. However, there are no guidelines for efficacious drugs against mucinous appendiceal adenocarcinoma. Therefore, relevant high-fidelity models should be investigated to identify effective drugs for individual therapy. Methods Surgical tumor specimens were obtained from a mucinous appendiceal adenocarcinoma patient. The tissue was digested and organoid culture was established. H&E and immunohistochemistry staining as well as DNA sequencing was performed on tissue and organoid. The pathological characteristics and gene mutations of the organoid were compared to those of the original tumor. Drug sensitivity tests were performed on organoid and the patient clinical responds to chemotherapy and targeted therapy was compared. Results Organoids were successfully established and stably passaged. Pathological characteristics of organoids including H&E staining and expression of protein markers (CK20, CDX-2, STAB2, CD7, PAX8) were consistent to those of the original tumor. Moreover, the organoids carried the same gene mutations as the primary tumor. Sensitivity of the organoids to chemotherapeutic drugs and tyrosine kinase inhibitors included: 5-FU (IC50 43.95 μM), Oxaliplatin (IC50 23.49 μM), SN38 (IC50 1.02 μM), Apatinib (IC50 0.10 μM), Dasatinib (IC50 2.27 μM), Docetaxel (IC50 5.26 μM), Regorafenib (IC50 18.90 μM), and Everolimus (IC50 9.20 μM). The sensitivities of organoid to these drugs were comparable to those of the patient's clinical responses. Conclusion The mucinous appendiceal adenocarcinoma organoid model which retained the characteristics of the primary tumor was successfully established. Combined organoid-based drug screening and high throughput sequencing provided a promising way for mucinous appendiceal adenocarcinoma treatment.